Study on candidate genes for milk production traits of Red Chittagong Cattle - Mostari, MP; Khan, MYA (Bangladesh Journal of Livestock Research, 2020)
The study was carried out on Stearoyl-CoA desaturase (SCD,) diacylglycerolacyltransferase-1 (DGAT1) and ATP-binding cassette G2 (ABCG2) genes which are responsible for variation in milk production traits (milk yield, fat yield, protein yield, and SNF yield) in cattle. These genes were used as candidate genes in Red Chittagong Cattle (RCC) breed of Bangladesh Livestock Research Institute (BLRI) herd for detection of single nucleotide polymorphisms (SNPs) causing variation in milk production traits. Focusing on the effects of SNPs on milk production traits, phenotypic variation within RCC breed was identified and categorized based on milk production traits. Average lactation yield varied from 527 to 1436 kg (n=29) per lactation. About 18% of lactating cows showed an average of >1000 kg per lactation. Average fat percent ranged from 4.71 to 6.25 (n=15). Eighteen (18) set of primers were designed to amplify targeted regions of SCD, DGAT1 and ABCG2 genes, where 8 set from DGAT1, 6 set from SCD and 4 set from ABCG2 gene. Pooled DNA from 50 RCC cows and 5 RCC bulls were used in sequencing. In sequence analysis, the SCD, DGAT1 and ABCG2 alleles found fixed in RCC. This study suggests an evidence that RCC breed has fixed alleles with respect to SCD, DGAT1 and ABCG2 genes reported to be responsible for higher milk fat yield, higher fat and protein percent. Bang. J. Livs. Res. Vol. 26 (1&2), 2019: P. 1-7